Causal effect of alcohol use on the risk of end-stage kidney disease and related comorbidities: a Mendelian randomization study - Sehoon Park; Soojin Lee; Yaerim Kim; Yeonhee Lee; Min Woo Kang; Kwangsoo Kim; Yong Chul Kim; Seung Seok Han; Hajeong Lee; Jung Pyo Lee; Kwon Wook Joo; Chun Soo Lim; et al. (The Korean Society of Nephrology, 2021)
Background An inverse observational association between alcohol use and the risk of chronic kidney disease (CKD) or end-stage kidney disease (ESKD) has been reported. The causal effect of alcohol use on the risk of ESKD warrants additional investigation. Methods The study was an observational cohort study investigating the UK Biobank and performed Mendelian randomization (MR) analysis. Amounts of alcohol use were collected using a touchscreen questionnaire. In the observational analysis, 212,133 participants without prevalent ESKD were studied, and the association between alcohol use and the risk of prevalent CKD or incident ESKD was investigated. The genetic analysis included 337,138 participants of white British ancestry. For one-sample MR, an analysis based on a polygenic risk score (PRS) was conducted with genetically predicted alcohol intake. The MR analysis investigated ESKD outcome and related comorbidities. Results Lower alcohol use was observationally associated with a higher risk of prevalent CKD or incident ESKD. However, the genetic risk of CKD was significantly associated with lower alcohol use, suggesting reverse causation. A higher PRS for alcohol use was significantly associated with a higher risk of ESKD (per units of one phenotypical alcohol drink; adjusted odds ratio of 1.16 [95% confidence interval, 1.02-1.31]) and related comorbidities, including hypertension, diabetes mellitus, obesity, and central obesity. Conclusion The inverse observational association between alcohol use and the risk of CKD or ESKD may have been affected by reverse causation. Our study supports a causal effect of alcohol use on a higher risk of ESKD and related predisposing comorbidities.